Neurotensin as Modulator of Basal Ganglia- Thalamocortical Motor Circuit – Emerging Evidence for Neurotensin NTS1 Receptor as a Potential Target in Parkinson's Disease - Ferraro, Luca; Antonelli, Tiziana; Beggiato, Sarah; Tomasini, Maria Cristina; Steardo, Antonio; Fuxe, Kjell; Tanganelli, Sergio (IntechOpen, 2012)
None